Kandungan Protein dan Indeks Glikemik Snack Bar Berbasis Kacang Gude dan Ubi Jalar Kuning - Afni, Nur; Riezka Zuhriatika Rasyda; Lingga Gita Dwikasari (Jurnal Inotera, 2026)
This study investigates the potential of Indonesia’s indigenous crops, pigeon pea and yellow sweet potato, for the development of nutritious snack bars with desirable protein content and glycemic index (GI). Eleven formulations with varying ratios of pigeon pea and yellow sweet potato (0%:100% to 100%:0%) were produced and analyzed for protein content using AOAC methods and for GI using glucose as the reference standard. Data were evaluated using one-way ANOVA followed by DMRT at a 5% significance level. Protein content ranged from 3.05 ± 0.01% to 13.64 ± 0.19%, while GI values spanned from 14.00 ± 0.65 to 76.00 ± 0.14. Increasing the proportion of pigeon pea resulted in a concurrent rise in both protein content and GI, indicating a strong positive correlation between these parameters and highlighting the challenge of formulating high-protein, low-GI snack bars from these ingredients. The findings indicate that thermal processing may enhance starch digestibility, thereby contributing to elevated GI in formulations with high pigeon pea content. A key limitation of this study is the absence of detailed analysis of processing-related factors such as heating intensity, matrix modification, and starch gelatinization that may influence glycemic response. Further investigation is required to elucidate these mechanisms.